2023
DOI: 10.1186/s12903-023-03519-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyaluronic acid gel and photobiomodulation therapy on wound healing after surgical gingivectomy: a randomized controlled clinical trial

Basma Khalil Yakout,
Fatma Ramzy Kamel,
Maha Abd El-Aziz Abou Khadr
et al.

Abstract: Background Surgical gingivectomy can be considered the gold standard treatment for gingival enlargement. The healing of wound site after gingivectomy occurs slowly by secondary intention. To accelerate the wound healing process, several studies have been conducted evaluating the effect of various treatment modalities. Photobiomodulation therapy (PBMT) was proposed to provide minimally invasive and painless treatment as well as to decrease discomfort of the patient following the surgical process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The flow chart describing the literature review process is shown in Figure 6 . Twenty-nine clinical studies were identified for full-text review, out of which one study was excluded due to a pediatric study population [ 24 ], and three more studies were excluded due to the additional use of photodynamic therapy [ 25 , 26 , 27 ]. The nature of local adjunctive therapy used in the 25 reviewed studies, along with the reported improvements in clinical parameters and study outcomes, are detailed in Table 1 .…”
Section: Systematic Review Of the Literature—methodology And Resultsmentioning
confidence: 99%
“…The flow chart describing the literature review process is shown in Figure 6 . Twenty-nine clinical studies were identified for full-text review, out of which one study was excluded due to a pediatric study population [ 24 ], and three more studies were excluded due to the additional use of photodynamic therapy [ 25 , 26 , 27 ]. The nature of local adjunctive therapy used in the 25 reviewed studies, along with the reported improvements in clinical parameters and study outcomes, are detailed in Table 1 .…”
Section: Systematic Review Of the Literature—methodology And Resultsmentioning
confidence: 99%